The problem of the business portfolio composing - Жданова, Олена Григорівна; Івченко, Олег Миколайович; Яворська, Катерина Юріївна (Technology audit and production reserves, 2013)
In the article the main marketing features of business portfolio evaluation process were shown. It was emphasized, that market correlation between business portfolio components is required to be mentioned during its balance estimation. In case it was figured out, those components (strategic business units (SBU) and supporting market activities) need to be in business directions organized. One of the effective ways of solving those business challenges is the algorithm of finding and forming balanced portfolio which was discribed in this article. To be successfully completed it should include the following input values: correlation matrix of SBU; the range within which the number of SBU in the portflio changes; the final number of optimal business portfolios.